2006
DOI: 10.1002/cncr.22105
|View full text |Cite
|
Sign up to set email alerts
|

Female gamete preservation

Abstract: The use of multiple agent chemotherapy and combined modality treatment of childhood and adolescent cancers has markedly increased survival rates. Thus, the majority of young cancer patients survive into adulthood and the potential long-term consequences of the therapies are of ongoing concern. Alkylating agents have proven to be the most toxic to the ovaries; however radiation is also extremely gonadotoxic. In addition, combination of these modalities will produce additive effects in terms of ovarian damage (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
0
15
0
1
Order By: Relevance
“…One of the commonly recognized side effects of cancer treatment in women is ovarian failure as a result of depletion of follicles (257, 258). For example, alkylating agents that are used for treatment of breast cancers are toxic to the ovary-particularly to primordial follicles, which constitute the ovarian reserve (259,260). Studies have also shown that women treated with both radiation below the diaphragm and alkylating agent chemotherapy are at greatest risk of having an accelerated menopause.…”
Section: Suggested Clinical Applications Of Our Current Knowledge mentioning
confidence: 99%
“…One of the commonly recognized side effects of cancer treatment in women is ovarian failure as a result of depletion of follicles (257, 258). For example, alkylating agents that are used for treatment of breast cancers are toxic to the ovary-particularly to primordial follicles, which constitute the ovarian reserve (259,260). Studies have also shown that women treated with both radiation below the diaphragm and alkylating agent chemotherapy are at greatest risk of having an accelerated menopause.…”
Section: Suggested Clinical Applications Of Our Current Knowledge mentioning
confidence: 99%
“…Irradiation of the ovaries will induce ovarian failure in almost 90% of women, as observed in childhood abdominal radiation [5]. Ovarian transposition, shielding, or transplantation can be offered to try and reduce the risk of radiation-induced ovarian damage but the efficacy of this intervention is variable and not well established [9]. With the wider availability of assisted reproductive technology, there are commonly opportunities for ovarian stimulation and oocyte or embryo cryopreservation prior to chemoradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Some anticancer drugs are well known to induce ovarian damage in addition to cancer cell death (1)(2)(3)(4)(5). Anticancer drugs may increase the apoptotic susceptibilities of normal ovarian follicles and cause granulosa cell apoptosis in ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in reproductive technology may provide help toward the preservation of fertility in such patients. Several studies have already evaluated the feasibilities of ovarian protection with concurrent hormone therapy, such as oral contraceptives (OCs) or gonadotropin-releasing hormone agonists (GnRHa), and clinical applications of assisted reproductive technology (ART), including embryo cryopreservation, oocyte cryopreservation, ovarian tissue cryopreservation and in vitro oocyte maturation (3)(4)(5). However, ovarian protection with OCs or GnRHa has not been completely established and its effects are currently insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation